Socialization in Creating Young Entrepreneurs in Villages to Increase the Purchasing Power of Village Communities When Budget Efficiency Occurs: Pengabdian - Kushariyadi; Purwaka Hari Prihanto; Mohammad Muslimin; Hartono; Nersiwad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This socialization was conducted by the author in several villages, namely Karanganyam Banyumas village, Mendalo Indah Jambi Luar Kota village, and Wonorejo Bantur Malang village with a minimum socialization period of three times in one month. The result in this conclusion show that if socialization increases interest in entrepreneurship, it can create young entrepreneurs, the creation of young entrepreneurs can increase income, increasing income can increase people's purchasing power. With increasing people's purchasing power, even if there is efficiency that has an impact on village funds or other assistance, rural communities will still be able to survive and fight for their survival.